Analisis Peramalan Penjualan untuk Perencanaan Produksi pada Lavanda Brownies Karawang - Atsila Nur Marda Sofwa; Dedi Mulyadi; Santi Pertiwi Hari Sandi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research was conducted at Lavanda Brownies Karawang which compared the moving average and exponential smoothing forecasting methods. This research aims to find out, calculate, analyze and explain how to use the moving average and exponential smoothing methods in sales forecasting for production planning at Lavanda Brownies Karawang as well as to find out, calculate, analyze and explain what forecasting method is most appropriate to use for Lavanda Brownies Karawang based on calculations of Mean Absolute Devitiation (MAD), Mean Square Error (MSE), and Mean Absolute Percent Error (MAPE). This research uses a quantitative descriptive method, to get a general picture of the company's condition, a literature review related to the research topic is carried out as well as field research through interviews and direct observation. Based on the research results, the exponential smoothing forecasting method based on alpha 0.9 is the best forecasting method for production planning. This method was chosen because it has the smallest MAD, MSE and MAPE accuracy values ​​when compared to other methods, namely with MAD of 489,909, MSE of 506.950 and a MAPE percentage of 14,14%, which percentage has the smallest value and is included in the category Good. A smaller MAPE accuracy value indicates more precise forecasting. Because in forecasting the smaller the accuracy value, the better the forecasting results so that the Lavanda Brownies business can plan optimal steamed brownie production activities in the next period.